FULFILLMENT OF HEALTH CARE RIGHTS FOR PRISONERS WITH TUBERCULOSIS IN CLASS IIB MENGGALA DETENTION CENTER - Riansyah, Muhammad Ridho; Santoso, Iman (Universitas Nusa Cendana, 2025)
This study examines the fulfillment of healthcare rights for prisoners with tuberculosis (TB) in the Class IIB Menggala Detention Center. The background highlights the critical need for adequate healthcare services for inmates, especially those suffering from communicable diseases like TB, which poses significant health risks. The objective is to assess the current state of healthcare provision and identify barriers to effective treatment. Using qualitative research methods, data were collected through observations and discussions to evaluate the available facilities, resources, and the effectiveness of healthcare management. The findings reveal that the detention center's healthcare services are suboptimal, characterized by insufficient medical facilities, limited medication availability, and inadequate human resources. These deficiencies hinder the provision of adequate care for TB-infected inmates, underscoring the necessity for government intervention to enhance healthcare services. The study concludes that a comprehensive approach is essential to uphold the health rights of prisoners. Keywords: Healthcare Rights; Tuberculosis; Prisoners